PENDAMPINGAN ATLET BOLA VOLLY DALAM PENANGANAN KASUS CIDERA MUSKULOSKELETAL DI TURNAMENT TABANAN OPEN CUP - ni luh, seri astuti (STIKES Advaita Medika Tabanan, 2023)
Background: Physical fitness is essential for all sports. The state of one's physical health greatly influences other factors like strength, strategy, and mentality. In order for athletes to perform at their best during competitions and physical duties, physical circumstances might have an impact. Muscleball competitions like the Tabanan Cup's are a crucial opportunity to handle situations that arise on-site.The purpose of this exercise is to help athletes manage musculoskeletal issues that may occur during volleyball matches. The implementation strategy is: Each participant in the activity has their vital signs checked before the game, and if they have an injury, they will receive quick medical attention. Results: Several incidences of musculoskeletal injuries were discovered while watching volleyball tournaments